Calcium Mass Balances in Bicarbonate Hemodialysis - Carlo Basile (International Journal of Nephrology)
Dialysate calcium (Ca) concentration should be viewed as part of the integrated therapeutic regimen to control renal osteodystrophy and maintain normal mineral metabolism. The goals of this integrated approach are to keep the patient in a mild positive Ca mass balance (CaMB), to maintain normal serum Ca levels, to control plasma parathyroid hormone values to two to three times above normal levels, and to avoid soft-tissue calcifications. Thus, a correct net CaMB during hemodialysis (HD) is crucial in the treatment of renal osteodystrophy. Very few studies have been published which measured CaMBs in bicarbonate HD. This is mainly due to the technical difficulties in achieving an accurate measurement of CaMBs owing to the need for the collection of the total spent dialysate or of a proportional aliquot of it. Whereas no doubt exists about the fact that an inlet dialysate Ca concentration (CaD) of 1.75 mmol/L leads to a positive CaMB, more controversial is this issue, when dealing with a CaD of 1.50 mmol/L and, even more, when dealing with a CaD of 1.25 mmol/L. Another important issue is the appropriate CaD in long-hour slow-flow nocturnal HD. Finally, which CaMB should we study: ionized CaMB or total CaMB? This issue is largely discussed in the review.